Interventions for necrotizing pancreatitis: an overview of current approaches. (July 2013) - Trikudanathan, Guru; Arain, Mustafa; Attam, Rajeev; Freeman, Martin L
The management of necrotizing pancreatitis has undergone a paradigm shift toward minimally invasive techniques for necrosectomy, obviating the need for open necrosectomy in most cases. There is increasing evidence that minimally invasive approaches including a step-up approach that incorporates percutaneous catheter or endoscopic transluminal drainage, followed by video-assisted retroperitoneal or endoscopic debridement are associated with improved outcomes over traditional open necrosectomy for patients with infected necrosis. A recent international multidisciplinary consensus conference emphasized the superiority of minimally invasive approaches over standard surgical approaches. The success of these techniques depends on concerted efforts of a multidisciplinary team of interventional endoscopists, radiologists, intensivists and surgeons dedicated to the management of severe acute pancreatitis and its complications. This review provides an overview of minimally invasive techniques for management of necrotizing pancreatitis, including indications, timing, advantages and disadvantages.